Periductal stromal sarcoma of the breast: A case report and review of the literature - LAN, YANDAN (D.A. Spandidos, 2014)
Periductal stromal sarcoma (PSS), spindle and epithelioid types, is a rare subtype of malignant fibroepithelial tumor. The morphological characteristics of this neoplasm are different from phyllodes tumor and stromal sarcoma. PSS exhibits biphasic histology with benign ductal elements and a sarcomatous stroma composed of spindle cells and lacking phyllodes tumor architecture. The therapeutic management of PSS is based on wide surgery with free margins, and adjuvant therapies are not required. To the best of our knowledge, the recurrence of PSS in ≤5 months has not been reported in the literature to date. This report describes a 43-year-old woman who presented to our hospital with a recurrence of nodules in the left breast. The patient had undergone lumpectomy at a different hospital 5 months previously, and a diagnosis of phyllodes tumor was pathologically confirmed. On presentation at our hospital, the patient underwent a second lumpectomy. Histological examination revealed PSS and the patient underwent a simple mastectomy of the left breast with no adjuvant treatment (such as chemotherapy or radiotherapy). After 9 months of close follow-up examinations, no recurrence was observed. PSS is an extremely rare disease with low-grade sarcomatous behavior, which may evolve into a phyllodes tumor or an entity of breast cancer. Therefore, frequent follow-up examinations are required.